Exploring Safety Management Dimensions in Sports: Insights for Public Health and Policy from a Content Analysis of Top-Ranked Articles - Azimi Nojadeh, Hamed; Abdavi, Fatemeh; Badriazarin, Yaghob (Journal of Foresight and Health Governance, 2025)
One of the main tenets of sustainable development in societies is public health, which refers to a collection of coordinated efforts to prevent illness, promote health, and enhance population-level quality of life. A thorough understanding of the different aspects of health, combined with a structured analysis of the factors that influence it—especially in areas like sports and physical activity—can play a crucial role in formulating effective strategies for promoting safety, reducing risks, and enhancing public health outcomes. Given the physical activities and intense competitions of athletes, maintaining their health and safety is of paramount importance. The main goal of this research is to identify the dimensions of safety management in sports by studying and analyzing the top ten reputable articles in this field published in the Scopus citation database. This research aims to promote this crucial area by identifying key principles and dimensions of safety management in sports and focusing on improving the safety and health of athletes as its primary objective. To achieve this goal, 214 international articles from various sources around the world that were published in the Scopus citation database were selected and examined. These articles were published between 1993 and 2023 and were studied and analyzed to extract dimensions and principles of safety management in sports through content analysis. In this research, specialized software such as Publish OR Perish, Excel, VOSviewer, RStudio, R, and Maxqda2020 was used for searching, identifying, and evaluating safety management elements in sports. The results of this content analysis led to the identification of eight dimensions in the field of safety management and sports, which were repeatedly mentioned in the top ten articles in this area. These dimensions include physical safety, medical safety, psychological safety, legal safety, tourist safety, education and training, risk management processes, and safety barriers. With these dimensions, safety can be significantly enhanced, and unforeseeable risks can be greatly reduced.